Comparison of step kinematics of active resisted 30 m sprints between experienced male and female sprinters - van den Tillaar, R. (Translational Sports Medicine, 2020)
This study compared the kinematics of unresisted and active resisted 30 m sprints with different loads in male and female sprinters. Step kinematics were measured in 14 male and 14 female participants during an unresisted 30 m sprint, and sprints with 10%, 20%, 30%, and 40% of body mass active resistance. Increased resisted loads resulted in slower 30 m times, which was the result of a lower step velocity, mainly caused by shorter step lengths and frequencies, flight times, and longer contact times. In addition, the resisted loads had a larger effect on women than men, as shown by a larger increase in sprint times. These time differences were the result of an earlier and slower maximal step velocity, which was mainly caused by longer contact times, shorter step lengths, and frequencies in women compared with men. Based upon these findings, it was concluded that when introducing active resisted sprints, women should sprint a shorter distance and/or have a lower resistance load than men, to prevent too much fatigue, and thereby avoid training for more endurance rather than acceleration ability. Furthermore, women should focus on increasing relative leg muscle mass to increase leg stiffness and their horizontal force production capacity.